Optimization of mooring configuration parameters of floating wave energy converts - Vicente, Pedro C. (2012)
Floating point absorbers devices are a large class of wave energy converters for deployment offshore, typically in water depths between 40 and 100m. As floating oil and gas platforms,the devices are subject to drift forces due to waves, currents and wind, and therefore have to be kept in place by a proper mooring system. Although similarities can be found between the energy converting systems and floating platforms, the mooring design requirements will have some important differences between them, one of them associated to the fact that, in the case of a wave energy converter, the mooring connections may significantly modify its energy absorption properties by interacting with its oscillations. It is therefore important to examine what might be the more suitable mooring design for wave energy devices, according to the converters specifications. When defining a mooring system for a device, several initial parameters have to be established, such as cable material and thickness, distance to the mooring point on the bottom, and which can influence the device performance in terms of motion,power output and survivability. Different parameters, for which acceptable intervals can be established, will represent different power absorptions,displacements from equilibrium position, load demands on the moorings and of course also different costs. The work presented here analyzes what might be, for wave energy converter floating point absorber, the optimal mooring configuration parameters, respecting certain pre-established acceptable intervals and using a time-domain model that takes into account the non-linearities introduced by the mooring system. Numerical results for the mooring forces demands and also motions and absorbed power, are presented for two different mooring configurations for a system consisting of a hemispherical buoy in regular waves and assuming a liner PTO.